Inequalities for eigenvalues of a system of higher-order differential equations - Sun, H.J. (Український математичний журнал, 2014)
We establish some sharper inequalities for eigenvalues of a system of higher-order differential equations. Moreover, we present some sharper estimates for the upper bound of the (k +1)th eigenvalue and the gaps of its consecutive eigenvalues.